PENGARUH REPUTASI PENJAMIN EMISI TERHADAP PENGELOLAAN LABA PADA PENAWARAN UMUM PERDANA SAHAM DI BURSA EFEK INDONESIA - Sabar Warsini; Aminah Fauzy (Ekonomi & Bisnis, 2011)
Abstract This research investigates the affects of underwriter reputation on the earnings management practice in the period of Initial Public Offering (IPO). This research is held to find out the empirical evidence in order to reply the three main problems exist. Firstly, do managers opportunistically manage earnings in the period of IPO? Secondly, how is the pattern of earnings management in the period of IPO? and thirdly, do underwriters with good reputation can lessen the existence of earnings management practice in the period of IPO? In this research earnings management is measured by discretionary accruals ( Dechow model,1995). Using a sample of 43 IPO’s over four-year period (2007-2010), we find that in the period of IPO, managers have manage earnings and the pattern of the earnings management is income increasing. Differ from result of previous research , we find that underwriter reputation is insignificantly influence earnings management practice in the period of IPO. Keyword : initial public offering, underwriter reputation, earnings management, discretionary accruals